Proceedings of the the 15th International Conference on Interaction Design and Children 2016
DOI: 10.1145/2930674.2930689
|View full text |Cite
|
Sign up to set email alerts
|

Andantino

Abstract: This paper explores how multi-modal body-syntonic interactive systems may be used to teach children to play the piano beyond the typical focus on reading musical scores and "surface correctness". Our work draws from Dalcroze Eurhythmics, a method of music pedagogy aimed at instilling an understanding of music rooted in the body. We present a Dalcrozian process of piano learning as a fivestep iterative cycle of: listen, internalize, extend, analyze, and improvise. As a case study of how digital technologies may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…This was influenced by the research of environmental psychologist McKenzie-Mohr who suggested that this age was the best time to help build "ecologically sustainable behaviour" in children [114]. Xiao et al [88] also focus on children between 7 and 13, as it was mentioned based on Piaget's observation that children between the ages of a toddler and up to 12 years old have not fully developed their abstract symbolic thinking. Still, the latter end of the spectrum had higher stage-like increases in abstract, symbolic understandings, while children at the lower end relied more on sensory-motor thinking.…”
Section: Children's Roles Age and Stages Of Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…This was influenced by the research of environmental psychologist McKenzie-Mohr who suggested that this age was the best time to help build "ecologically sustainable behaviour" in children [114]. Xiao et al [88] also focus on children between 7 and 13, as it was mentioned based on Piaget's observation that children between the ages of a toddler and up to 12 years old have not fully developed their abstract symbolic thinking. Still, the latter end of the spectrum had higher stage-like increases in abstract, symbolic understandings, while children at the lower end relied more on sensory-motor thinking.…”
Section: Children's Roles Age and Stages Of Developmentmentioning
confidence: 99%
“…or programming [107,104,102], with few studies exploring the arts, such as music, independent of STEM knowledge -Andantino [88] being an excellent example of that. We find that other studies involving design and other arts only used it as a teaching method for a more STEM-related goal rather than as the sole purpose of engagement.…”
Section: Subjects Focused On In Embodied Learning Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Musical interfaces can be used to exchange music between the user and an interactive interface. They include digital musical instruments, augmented traditional instruments, or interactive installations [17,18,25,35]. For example, Andantino [35] is a piano augmented with a projection of animated figures representing musical elements such as sound quality, moods in the music or harmonies.…”
Section: Musical Interfaces To Support Neurodiverse Users and Child Developmentmentioning
confidence: 99%